Teachers as Learning Media Designers: Transforming Knowledge into Practice Through Community Service - Fadhlan Muchlas Abrori; Nursia Nursia; Fitri Wijarini; Alfi Suciyati; Silfia Ilma; Nur Fitriana Sam; Vlorensius Vlorensius; Ibrahim Ibrahim; Bimo Aji Nugroho; Yogho Prastyo; Ermawaty Maradhy; Darius Rupa; Listiani Listiani; Fatmawati Fatmawati; Zulfadli Zulfadli (TAAWUN, 2026)
The majority of teacher problems in Indonesia are related to pedagogical and professional competencies. One of these is the problem of developing media independently. This community service program is a solution for community service partners (in this context, elementary school teachers) to improve their media development skills. There are three main stages in this activity: outreach, mentoring, and media dissemination. This activity also investigated the Reflective Mapping of the Teacher's Resource System (RMRS) to identify how teachers manage the resources used to develop learning media. The outcome of this service is improved teachers' ability to develop media. Three of the fifteen teachers disseminated the media they developed. Based on analysis of dissemination and interviews with teachers, the RMRS results indicate that teachers have a variety of resources for media development. The findings of these activities indicate that this program not only contributes to media product output but also to understanding teachers’ resource-management mindsets, grounded in pedagogical rationality and connections among resources. Overall, this activity is oriented toward design-related processes rather than merely improving technical skills in media development. These activities emphasize ongoing professional teacher development and foster a systematic, holistic perspective on the organization and use of resources in media development.